2015
DOI: 10.1590/2179-8087.078214
|View full text |Cite
|
Sign up to set email alerts
|

Fauna de Coleoptera Edáfica em Eucalipto sob Diferentes Sistemas de Controle Químico da Matocompetição

Abstract: RESUMOO Eucalyptus grandis destaca-se como uma das espécies mais cultivadas no Brasil em razão de sua produtividade e da qualidade da madeira. Objetivou-se com este estudo avaliar a coleopterofauna edáfica em um plantio inicial de E. grandis sob diferentes sistemas de controle de plantas daninhas em Santa Maria, RS, utilizando-se armadilhas de solo. Os tratamentos avaliados basearam-se no controle químico de plantas daninhas: total, na linha e entrelinha de plantio (CT); total, na linha de plantio (CL); monoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
7
0
7
Order By: Relevance
“…In this sense, the greater and lesser density of edaphic fauna found in April/2013 and January/2014 (Table 3), respectively, is justified in part. A number of researchers have reported on the relationship of SM to the diversity and density of the fauna (CUNHA-NETO et al 2012;ABREU et al 2014;GARLET et al 2015). Machado et al (2015) reported the highest number of organisms during periods of higher rainfall, but when they investigated the edaphic fauna in a fragment of the Semideciduous Seasonal Forest in Rio de Janeiro, they found fewer faunal representatives in the dry season, as it also was found in this inquire.…”
Section: Accessory Variablesmentioning
confidence: 57%
“…In this sense, the greater and lesser density of edaphic fauna found in April/2013 and January/2014 (Table 3), respectively, is justified in part. A number of researchers have reported on the relationship of SM to the diversity and density of the fauna (CUNHA-NETO et al 2012;ABREU et al 2014;GARLET et al 2015). Machado et al (2015) reported the highest number of organisms during periods of higher rainfall, but when they investigated the edaphic fauna in a fragment of the Semideciduous Seasonal Forest in Rio de Janeiro, they found fewer faunal representatives in the dry season, as it also was found in this inquire.…”
Section: Accessory Variablesmentioning
confidence: 57%
“…Assim, os tratamentos foram repetidos toda vez que a infestação ultrapassou 25% da área da parcela. Todos os tratamentos receberam aplicações nas mesmas datas (Garlet et al, 2015).…”
Section: P B Funclassified
“…Algumas famílias dessa ordem sofrem alterações na sua comunidade principalmente decorrentes de mudanças microclimáticas, sendo sensíveis indicadores de temperatura e umidade (GARLET et al, 2015). Além disso, os decompositores primários (Molusca, Blattodea e Isopoda) estão mais relacionados a FN (Figuras 1 e Tabela 3) em função da diversidade e quantidade de material vegetal depositado.…”
Section: Análise De Composição Da Comunidadeunclassified